Red list of threatened vascular plants in Italy. (13th January 2021) - Orsenigo, Simone; Fenu, Giuseppe; Gargano, Domenico; Montagnani, Chiara; Abeli, Thomas; Alessandrini, Alessandro; Bacchetta, Gianluigi; Bartolucci, Fabrizio; Carta, Angelino; Castello, Miris; Cogoni, Donatella; Conti, Fabio; et al.
Abstract: Italy has a rich natural heritage, which is dangerously under pressure. In recent years, there is an increased awareness of the crucial role of plants in ecosystem functioning and in providing ecosystem services. Consequently, an updated Red List of the Italian vascular flora was compiled in this work, at the request of the Ministry for Environment, Land and Sea Protection, with the scientific support of the Italian Botanical Society. The IUCN Red List criteria were applied to 2, 430 Italian native vascular plant taxa to assess their current extinction risk and to highlight the major threats affecting the Italian flora. Our results revealed that 54 taxa (2.2% of the assessed taxa) are extinct or possibly extinct at regional level, while 590 taxa (24.3%) were assigned to a risk category. Moreover, 404 taxa (16.6%) were categorized as Data Deficient. The Italian vascular flora is primarily threatened by habitat modifications due to anthropic disturbance and, especially, to agriculture, tourism and residential development. Coastal areas and lowlands, where anthropogenic impacts and ecosystem destruction are more pronounced, host the greatest number of extinct or declining taxa. Our results represent an important baseline to establish conservation priorities, legislative choices and intervention strategies on a national scale.